Models FRBR and FRAD - Rifqa Shadrina (UIN Sumatera Utara, 2016)
This article discusses FRBR and FRAD is an important foundation of the development of the RDA. Therefore, to understand the concept of FRBR and FRAD RDA then learning becomes easier because the vocabulary, content, and organization of the RDA using FRBR and FRAD model